A Pair-wise Analysis of Intra-city Price Convergence Within the Paris Housing Market (2017)
We examine long-run house price convergence across the twenty Paris districts using a quarterly dataset that spans from 1991 to 2014. Our approach is based on two stages. In the first stage, we apply methods of unit root testing. Our econometric modelling exercise adopts a pair wise approach that is built on a probabilistic test for convergence based on all house price differentials across the Paris districts. We find that more than 50 % of the intra-city house price differentials that can be computed are stationary. In the second stage of our investigation, we analyse the drivers of convergence. The probability of stationarity is negatively affected by unemployment differentials across districts, demographics differentials and supply-side characteristics. Our findings further reveal that the half-life of a shock to long-run price equilibrium is affected positively by unemployment, distance and housing supply. Our analysis suggests that smaller distances between Parisian districts are associated with a faster speed of adjustment back towards long-run equilibrium. © 2015, Springer Science+Business Media New York.